Penerapan Jaringan Sensor Nirkabel dan Internet of Things (IoT) pada Pertanian Terpadu - Suhardi; Dedi Triyanto; Irma Nirmala (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Integrated farming system is an approach to managing plants, livestock, and fish along with their environment to create optimal results. The development of integrated agriculture is advancing with technologies such as Wireless Sensor Networks and the Internet of Things (IoT), enabling remote monitoring and control of agricultural environmental conditions. For this purpose, an application called "Integrated Farming System based on Wireless Sensor Networks and the Internet of Things (IoT)" has been developed. The system takes the form of aquaponics, consisting of areas for cultivating plants and ponds for fish farming, using subjects like Pakcoy plants and Nile tilapia fish. This system has been successfully implemented, reading water conditions including temperature and pH, as well as air conditions such as temperature and humidity. Moreover, the system can also monitor the status of the water pump used to channel water from the pond to the pipes, and it can control feeding in the livestock. Monitoring and control processes within this system are carried out using a website application.